1989
DOI: 10.1177/002199838902300701
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Strength of Graphite/Epoxy Bolted Joints by Introducing an Adhesively Bonded Metallic Insert

Abstract: In this paper a method to increase the failure load in graphite/epoxy bolted joints where the failure mode is bearing strength is proposed by bonding a metallic insert in the hole. In order to design test specimens with significantly reduced compressive stresses at the hole boundary, finite element (FE) analysis was performed. The FE analysis revealed the possibility to reduce the compressive stresses at the hole boundary in quasi-isotropic laminate by approximately 50%, if a 10 mm hole is enlarged to 14 mm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…It is clearly observed from the table that the metal inserts have increased the failure load for each joint configuration. Similar trends have been reported for the bolt joint in previous study 1,18 . Figure 6 shows the effect of E/D and W/D ratios on the ultimate failure loads for the specimens with and without the metal inserts.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…It is clearly observed from the table that the metal inserts have increased the failure load for each joint configuration. Similar trends have been reported for the bolt joint in previous study 1,18 . Figure 6 shows the effect of E/D and W/D ratios on the ultimate failure loads for the specimens with and without the metal inserts.…”
Section: Resultssupporting
confidence: 91%
“…Table 4 summarises the failure modes for different pin joint configurations, where S, N and B signifies the shear-out, net-tension and bearing type of failure modes. Introducing the metal inserts in the composite joint change the failure modes of the joints 1 . Table 4 shows that for the lower values of W/D ratios, different failure mode i.e., net-tension is observed for the specimens with the metal inserts as compared to the specimens without the metal inserts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete test procedures and results are presented in the thesis from which this paper is extracted [5,20]. This concept of reinforcement by introduction of an adhesively bonded metallic insert in graphite/epoxy joints was also discussed in a recent paper by Nilsson [21]. He used finite element techniques to demonstrate how the high compressive stresses in the laminate could be reduced by bonding a stiff metallic insert into the hole.…”
Section: Stress and Strain Relief By The Use Of Isotropic Materials Inmentioning
confidence: 99%
“…A theoretical and experimental investigation by Nilsson (1989) on increasing the bearing strength of composite bolted joints showed that by bonding a 2 mm circular metallic insert in the hole, the compressive stresses at the hole boundary were reduced by 50% and the failure load was increased by up to 55%. The purpose of this example is to optimize the shape of the insert by an optimized material distribution using ITD algorithm.…”
Section: Metallic Insertmentioning
confidence: 99%